Alteration of renal cyclooxygenase expression due to partial unilateral ureteral obstruction in neonatal - Li, Zhi Qin; Zhang, Yi; Li, Qi; Wu, Shu Huan; Sun, Chang Yu; Yu, Zu Jiang (Canadian Urological Association Journal, 2013)
Introduction: Impaired renal water handling in response to neonatally-induced partial unilateral ureteral obstruction (PUUO) may be associated with altered expression of cyclooxygenase (COX). The purpose of the present study was to examine whether long-term PUUO induced at birth was associated with changes of COX-2. Methods: Rats were subjected to PUUO (n = 14) or a sham operation (n = 12) within the first 48 hours of life. The rats were divided into 4 groups: (1) PUUO at 9 weeks (n = 7); (2) the sham operation at 9 weeks (n = 6); (3) PUUO at 15 weeks (n = 7); and (4) the sham operation at 15 weeks (n = 6). Urine and blood samples were collected before sacrificing the animals. Plasma potassium, creatinine and urea, as well as the osmolality and sodium of plasma and urine were tested in each sample. The expression of renal COX-1 and COX-2 was examined at 9 and 15 weeks in rats with neonatally inducedPUUO within the first 48 hours of life by immunoblotting and immunocytochemistry. Results: PUUO caused a marked decrease in urine osmolality and a significant increase in urinary sodium of the obstructed kidney compared with the sham-operated kidney at 9 and 15 weeks. Immunoblotting analysis showed that an abundance of COX-2 in the obstructed kidney significantly increased compared with the non-obstructed kidney and sham-operated kidney at 9 weeks (p < 0.05) and 15 weeks (p < 0.05) in rats with PUUO. In contrast, COX-1 abundance in the obstructed kidney was similar to that in the non-obstructed kidney. Immunocytochemistry confirmed these findings. Conclusion: Renal COX-2 expression in the obstructed kidney is significantly altered in response to neonatally-induced PUUO. A marked increase in COX-2 indicates that it may be an important factor in reducing renal handling of sodium and water in response to PUUO.